(untitled) (American Journal of Islam and Society, 2003)
Islamic Banking is an outstanding example of collaboration among Muslim and non-Muslim scholars interested in integrating "Western-based literature with that developed in the Islamic tradition." Stating that Islamic banking, although widespread, remains "poorly understood" in the Muslim world and an "enigma" in the West, the authors seek to clarify many matters. The book’s main themes are Christian and Islamic positions on usurylriba’ (chapter 8); the foundations (chapters 2 and 3), theories (chapter 5), application (chapters 5, 6, 7, and 9), and progress (chapters I and 9) of Islamic banking; and an analysis of Islamic banking in light of current theories of financial intermediation (chapter 4) and corporate governance (chapter 7). The book highlights Islamic and Christian commonalities on issues pertinent to banking and finance. While stating that Christianity, Hinduism, Judaism, and Islam prohibit usury, "Islam is the only major religion which maintains a prohibition on usury" due to its prominence in the Qur’an. The issue of riba’ is perplexing, for despite warnings of severe consequences to those who engage in it, the Qur’an is silent on its exact nature. Unfortunately, successive generations of scholars have so confused matters that no one can say exactly what riba’ is. For example, a majority of scholars regarded bank interest as riba’ and, therefore, made the need for an interest-free Islamic banking system inevitable, whereas 21 jurists at Egypt’s al-Azhar recently proclaimed a ruling that legitimizes interest ...